Evaluating the Impact of Pavement Surface Condition on Vehicle Speed and Vehicle Operating Cost: A Case Study of Prithvi and B.P. Highways - Sitaula, Prakash Chandra; Gautam, Gopal; Bajracharya, Nhuja (Journal on Transportation System and Engineering, 2026)
Pavement surface condition plays a vital role in traffic flow, road safety, and vehicle operating costs (VOC), particularly on highways in developing countries like Nepal, where road transport is the primary mode of mobility. This research explores the relationship between pavement condition, vehicle speed, and VOC on specific sections of the Prithvi Highway and B.P. Highway. Pavement condition was assessed using the Pavement Condition Index (PCI), derived from detailed visual distress surveys conducted in accordance with ASTM D6433. Eighteen segments—fifteen on the Prithvi Highway and three on the B.P. Highway—were evaluated, with PCI scores ranging from 11 (serious deterioration) to 89 (excellent). Vehicle speeds were recorded via the spot speed method and analyzed based on the 85th percentile speed for three vehicle categories: two-wheelers, light vehicles, and heavy vehicles. The results reveal a strong positive correlation between PCI and operating speed, with significant speed reductions as pavement quality declines. Specifically, the decrease in speed from satisfactory to serious pavement conditions was about 44% for two-wheelers, 56% for light vehicles, and 60% for heavy vehicles. Polynomial regression models most effectively described the PCI–speed relationship, with R² values around 0.85–0.86. Vehicle operating costs were estimated using unit VOC rates recommended by JICA. The findings show that poor pavement conditions considerably increase VOC, especially for heavy vehicles, adding up to NPR 26 per km on severely deteriorated pavements. These results highlight the critical need to maintain good pavement conditions to improve traffic flow and reduce user costs, offering guidance for pavement management planning.